0844 AGE-RELATED EFFECTS ON SLEEP LOSS IN WAKING EEG CONNECTIVITY. (28th April 2017) - Rosinvil, T; Bouvier, J; Fortin, M; Robillard, R; Bouchard, M; Gaudet-Fex, B; Gaudreault, P; Dubé, J; Gosselin, N; Lina, J; Carrier, J
Abstract: Introduction: Research report robust change in functional connectivity (FC) during waking resting state after sleep loss. Studies indicate that older participants show smaller or similar effects to acute sleep loss on vigilance and cognition as compared to the young. However, age-related effects of sleep loss on FC have not been reported. The present study compared waking EEG connectivity before and after sleep deprivation in young and elderly adults. Methods: Thirteen young (9W;20-28y.o., mean=24.3 ± 2.7) and 12 elderly (6W;60–70 y.o., mean=64.1 ± 3.4) healthy subjects were sleep deprived for 26 hours. Two waking EEGs were recorded; the first after 10 minutes of wakefulness and the second after 24 hours of wakefulness. In both age groups, imaginary coherence (Fisher transformed) differences between the two experimental conditions were assessed with a standardized Z-stat. A non-parametric test on the max-stat and a permutation resampling allowed to account for multiple comparisons (between pairs of electrodes) in a FDR like thresholding for significance(p<.05). These analyses were performed in the anterior-posterior axis (Frontal, Central, Parietal, Occipital) for delta, theta, alpha, and beta bands. Results: In the elderly, sleep loss induced an increase of imaginary coherence as compared to rested wakefulness in delta between central and parietal derivations, in alpha and theta between frontal, parietal and occipital derivations, and in beta between most derivations. In the young, sleep loss induced an increase in coherence in delta between parietal and occipital derivations and in beta between frontal and parietal derivations. When comparing the two age groups, young subjects showed significantly stronger increase in coherence after sleep loss in delta(P3-O1, P4-O1). However, older individuals showed stronger increase in coherence in theta(F3-F4, F3-P3) and beta(F4-O2). Conclusion: Sleep loss increased EEG FC. Stronger impact of sleep loss in delta for the young subjects supports the idea that they are more sensitive to the accumulation of wakefulness than older individuals. Interestingly, older subjects show stronger effects of the deprivation in theta and beta. This may reflect an adaptive mechanism to sustain performance level. Future analyses will evaluate how changes in FC under sleep loss are linked to performance detriment. Support (If Any): NSERC, FRQ-NT, CIHR & FRQ-S.